Low-hardness high-temperature-resistant thermoplastic elastomer and preparation method thereof

By introducing urea groups into TPE materials to form hydrogen bonds and combining the use of white oil and polypropylene, the problem of taking into account the existing TPE materials between low hardness and high temperature resistance is solved, and the material is realized under high temperature conditions. Stable performance.

CN119410095APending Publication Date: 2025-02-11KUNSHAN KEXIN MACROMOLECULE MATERIAL CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411343461.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

While pursuing low hardness, existing TPE materials are difficult to take into account the long-term high temperature resistance requirements, which leads to softening and deformation under high temperature conditions, affecting the sealing effect and service life.

Method used

By modifying styrene-ethylene-butene-styrene block copolymer (SEBS), it introduces urea groups to form hydrogen bonds, and combines the use of white oil and polypropylene, reducing material hardness and improving high temperature resistance.

Benefits of technology

It achieves the high-temperature resistance of the material while maintaining low hardness, and extends the service life of the material under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005060337080000071
    Figure BDA0005060337080000071
  • Figure BDA0005060337080000081
    Figure BDA0005060337080000081
Patent Text Reader

Abstract

The invention relates to the field of thermoplastic elastomers, and particularly discloses a low-hardness high-temperature-resistant thermoplastic elastomer and a preparation method thereof. The low-hardness high-temperature-resistant thermoplastic elastomer is prepared from the following raw materials in parts by weight: 90 to 100 parts of modified styrene-ethylene-butylene-styrene block copolymer, 50 to 250 parts of white oil, 10 to 100 parts of polypropylene and 5 to 10 parts of antioxidant, and hydrogen bonds formed by ureido groups are introduced into the modified styrene-ethylene-butylene-styrene block copolymer; the preparation method comprises the following steps: uniformly mixing the styrene-ethylene-butylene-styrene block copolymer and the white oil at a high speed to prepare oil-filled SBES for later use; and pre-mixing the prepared oil-filled SBES, an antioxidant and polypropylene, and carrying out melt blending and extrusion granulation at 200-220 DEG C. The preparation method comprises the following steps: pre-mixing the oil-filled SBES, the antioxidant and the polypropylene; the composition can be used for product sealing, and has the advantages of high temperature resistance and low hardness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of thermoplastic elastomers, and more specifically, to a low-hardness, high-temperature-resistant thermoplastic elastomer and a preparation method thereof. Background Art

[0002] In industrial applications that require sealing, TPE materials must not only have low hardness and good elasticity, but also maintain stable physical and chemical properties under high temperature conditions to prevent leakage and failure.

[0003] At present, the TPE materials in the industry are pursuing low hardness while it is difficult to take into account the requirements of long-term high temperature resistance, which has become a key bottleneck restricting its widespread application in the field of high-end sealing. Although the existing TPE materials can reduce the hardness by adjusting the formula, they often sacrifice the heat resistance, resulting in easy softening and deformation under high temperature conditions, affecting the sealing effect and service life. Therefore, the development of a thermoplastic elastomer material that can maintain low hardness and have excellent high temperature resistance has become a technical problem that needs to be solved urgently. Summary of the invention

[0004] In order to improve the high temperature resistance of a low hardness thermoplastic elastomer, the present application provides a low hardness high temperature resistant thermoplastic elastomer and a preparation method thereof.

[0005] In a first aspect, the present application provides a low-hardness, high-temperature-resistant thermoplastic elastomer, which adopts the following technical solution: A low-hardness, high-temperature-resistant thermoplastic elastomer comprises the following raw materials in parts by weight: 90-100 parts of modified styrene-ethylene-butylene-styrene block copolymer, 50-250 parts of white oil, 10-100 parts of polypropylene, and 5-10 parts of antioxidant, wherein hydrogen bonds formed by urea groups are introduced into the modified styrene-ethylene-butylene-styrene block copolymer, and the preparation comprises the following steps: (1) dissolving styrene-ethylene-butylene-styrene block copolymer in xylene, heating to 110-130° C. with stirring, adding acrylate and initiator, stirring for 1-2 hours, and after the reaction, pouring the mixture into acetone with stirring, filtering, washing, and drying to obtain a preliminarily modified SEBS; (2) The preliminarily modified SEBS obtained in step (1) is immersed in dichloromethane. After 3-4 hours, the swollen SEBS is transferred to a dichloromethane solution of 4-phenyl-1,2,4-triazolin-3,5-dione. After sufficient reaction for 11-13 hours, the SEBS is taken out, washed and vacuum dried to obtain the modified styrene-ethylene-butylene-styrene block copolymer.

[0006] By adopting the above technical solution, SEBS as a base material has good elasticity and high temperature resistance. The addition of white oil as a softener can penetrate between SEBS molecular chains, reduce the interaction between molecular chains, and thus reduce the hardness of the elastomer. Further, by introducing urea groups into the SEBS molecular chain, the nitrogen atoms and hydrogen atoms in the urea groups can form hydrogen bonds with oxygen, nitrogen and other atoms in the SEBS molecular chain. The formed hydrogen bonds can enhance the interaction between molecules, thereby improving the high temperature resistance of the material.

[0007] Polypropylene and SEBS form a continuous cross-linked network, which are intertwined to form an interpenetrating network. At the same time, SEBS forms a dual continuous phase structure in the process of blending with polypropylene at the microscopic level. With the introduction of sacrificial hydrogen bonds, heat accumulates on the sacrificial hydrogen bonds and is released after breaking, which reduces the stress on the continuous network structure formed by SEBS and polypropylene, protects the main chain, and improves the high temperature resistance of the elastomer.

[0008] In the preparation process of the modified styrene-ethylene-butylene-styrene block copolymer, the initiator decomposes at high temperature to generate free radicals, which in turn triggers a free radical graft copolymerization reaction between the acrylate and the styrene chain segment in SEBS to form a graft chain, and introduces a double-bonded side chain into the SEBS main chain. The initial modified SEBS is soaked in dichloromethane to swell and increase the distance between the SEBS molecular chains, which is conducive to the subsequent reaction. Further, the triazolinedione and the double bond click chemical reaction react on the SEBS chain segment to form a urea group, and then form a hydrogen bond. In the subsequent cross-linking reaction, a sacrificial bond of a hydrogen bond cluster will be formed. This sacrificial bond can dissipate a large amount of energy. When subjected to high temperature, the energy inside the molecule increases, which easily leads to the breaking of some chemical bonds. The hydrogen bond cluster as a sacrificial bond will break before the covalent bond network, destroying and consuming a large amount of high-temperature energy, reducing the energy transferred to the polymer main chain, thereby improving the heat resistance of the material.

[0009] Optionally, the weight ratio of the styrene-ethylene-butylene-styrene block copolymer, acrylate, initiator and 4-phenyl-1,2,4-triazolidine-3,5-dione is 1:0.6-0.8:0.01-0.02:0.4-0.6.

[0010] Optionally, the acrylate is any one of ethyl acrylate or butyl acrylate.

[0011] By adopting the above technical solution, selecting acrylic acid ester with low glass transition temperature as raw material to be added to thermoplastic elastomer helps to reduce the glass transition temperature of the obtained thermoplastic elastomer, so that the elastomer can maintain a rubber state in a wider temperature range, that is, have a lower hardness. Further, ethyl acrylate and butyl acrylate are introduced into the copolymer chain segment, and the carbon-carbon chain segment thereon can provide good flexibility and chain segment mobility for the elastomer, making the polymer chain more easily deformed when subjected to external force, thereby further reducing the hardness of the material.

[0012] Optionally, the initiator is benzoyl peroxide.

[0013] By adopting the above technical scheme, benzoyl peroxide can effectively decompose to generate free radicals at an appropriate temperature, thereby initiating the grafting reaction of acrylate and SEBS and improving the efficiency of the modification reaction. Compared with some traditional initiators, the decomposition rate of benzoyl peroxide is relatively moderate, which is conducive to controlling the progress of the grafting reaction and the structure of the product, thereby obtaining a modified SEBS with uniform structure and stable performance, providing a good basis for the introduction of further groups.

[0014] Optionally, the antioxidant is a composite antioxidant obtained by mixing powdered phosphite and hindered phenol antioxidant in a weight ratio of 0.5:(2-3).

[0015] By adopting the above technical scheme and adding the above composite antioxidant, the hindered phenol antioxidant has good thermal stability, which can improve the high temperature resistance of the material. When used in combination with phosphite, the hindered phenol antioxidant first captures and removes free radicals, converts them into hydroperoxides, and eliminates the destructive effect of free radicals on the polymer. The phosphite further decomposes the hydroperoxides to prevent the hydroperoxides from being heated to form free radicals again to attack the elastomer, thereby effectively inhibiting the oxidative decomposition of the elastomer and improving the heat resistance of the elastomer.

[0016] Optionally, the raw materials also include 1-3 parts of sepiolite powder.

[0017] By adopting the above technical solution, sepiolite is a magnesium-rich fibrous silicate clay mineral with a natural micro-fibrous structure and octahedral discontinuous layers extending along the fiber axis. This structure gives it excellent adsorption and dispersibility, and can form a three-dimensional network structure, which forms a good interface bond with the matrix material, improves the tensile strength of the elastomer, and its micro-fibrous structure can disperse stress, thereby having a more stable structure, which can further help improve the high temperature resistance of the elastomer.

[0018] In a second aspect, the present application provides a method for preparing a low-hardness, high-temperature resistant thermoplastic elastomer, using the following technical solution: A method for preparing a low-hardness, high-temperature-resistant thermoplastic elastomer comprises the following preparation steps: (1) mixing styrene-ethylene-butylene-styrene block copolymer and white oil at high speed to obtain oil-extended SBES for later use; (2) The oil-filled SBES, antioxidant and polypropylene are weighed in proportion, pre-mixed, melt-blended and extruded into pellets at 200-220°C.

[0019] In summary, this application has the following beneficial effects: 1. Since the present application introduces urea groups into styrene-ethylene-butylene-styrene block copolymer (SEBS) by modifying it, hydrogen bond clusters are formed in the subsequent melt cross-linking, which effectively reduces the hardness of the elastomer on the one hand, and on the other hand, as a sacrificial bond, breaks before the main chain when subjected to high temperature, thereby improving the high temperature resistance of the material.

[0020] 2. The application adds composite antioxidants and sepiolite powder, which not only improves the thermal stability of the material, but also increases the tensile strength of the elastomer, making it have a more stable structure and better high temperature resistance. DETAILED DESCRIPTION

[0021] The present application is further described in detail below with reference to the embodiments.

[0022] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0023] Styrene-ethylene-butylene-styrene block copolymer was purchased from Dongguan Shengli New Materials Co., Ltd., brand G1650M; sepiolite powder was purchased from Neixiang Xinglei Sepiolite Co., Ltd., particle size 400μm, SiO2 content 57.28%; Preparation examples of raw materials and / or intermediates Preparation Example 1 A modified styrene-ethylene-butylene-styrene block copolymer, the preparation of which comprises the following steps: (1) Dissolve 100 kg of styrene-ethylene-butylene-styrene block copolymer in xylene, slowly heat to 120°C and stir. When SEBS is completely dissolved, add 60 kg of ethyl acrylate and quickly add 2 kg of benzoyl peroxide (initiator). Stir and react for 1.5 hours to ensure that the temperature and stirring speed in the reactor are stable to avoid local overheating or uneven stirring. After the reaction is completed, pour the mixture into acetone and stir. During the stirring process, the initially modified SEBS will gradually precipitate. Filter and collect the precipitate, wash it repeatedly with acetone and deionized water for 3-5 times, and vacuum dry it to obtain the initially modified SEBS. (2) The SEBS prepared above is immersed in dichloromethane, and after 3.5 hours, the swollen SEBS is moved to a dichloromethane solution containing 50 kg of 4-phenyl-1,2,4-triazolidine-3,5-dione, and after sufficient reaction for 12 hours, it is taken out, washed with dichloromethane and deionized water, and then vacuum dried to obtain the modified styrene-ethylene-butylene-styrene block copolymer. Xylene and dichloromethane are used as solvents, and the amount is based on the amount that can fully dissolve or immerse the raw materials.

[0024] Preparation Example 2 A modified styrene-ethylene-butylene-styrene block copolymer, the preparation of which comprises the following steps: (1) Dissolve 100 kg of styrene-ethylene-butylene-styrene block copolymer in xylene, slowly heat to 110°C and stir. When SEBS is completely dissolved, add 70 kg of ethyl acrylate and quickly add 4 kg of benzoyl peroxide (initiator). Stir and react for 1 hour to ensure that the temperature and stirring speed in the reactor are stable to avoid local overheating or uneven stirring. After the reaction is completed, pour the mixture into acetone and stir. During the stirring process, the initially modified SEBS will gradually precipitate. Filter and collect the precipitate, wash it repeatedly with acetone and deionized water for 3-5 times, and vacuum dry it to obtain the initially modified SEBS. (2) The SEBS prepared above is immersed in dichloromethane, and after 4 hours, the swollen SEBS is moved to a dichloromethane solution containing 60 kg of 4-phenyl-1,2,4-triazolidine-3,5-dione, and after sufficient reaction for 11 hours, it is taken out, washed with dichloromethane and deionized water, and then vacuum dried to obtain the modified styrene-ethylene-butylene-styrene block copolymer. Xylene and dichloromethane are used as solvents, and the amount is based on the amount that can fully dissolve or immerse the raw materials.

[0025] Preparation Example 3 A modified styrene-ethylene-butylene-styrene block copolymer, the preparation of which comprises the following steps: (1) Dissolve 100 kg of styrene-ethylene-butylene-styrene block copolymer in xylene, slowly heat to 130°C and stir. When SEBS is completely dissolved, add 80 kg of ethyl acrylate and quickly add 3 kg of benzoyl peroxide (initiator). Stir and react for 2 hours to ensure that the temperature and stirring speed in the reactor are stable to avoid local overheating or uneven stirring. After the reaction is completed, pour the mixture into acetone and stir. During the stirring process, the initially modified SEBS will gradually precipitate. Filter and collect the precipitate, wash it repeatedly with acetone and deionized water for 3-5 times, and vacuum dry it to obtain the initially modified SEBS. (2) The SEBS prepared above is immersed in dichloromethane, and after 3 hours, the swollen SEBS is moved to a dichloromethane solution containing 40 kg of 4-phenyl-1,2,4-triazolidine-3,5-dione, and after sufficient reaction for 13 hours, it is taken out, washed with dichloromethane and deionized water, and then vacuum dried to obtain the modified styrene-ethylene-butylene-styrene block copolymer. Xylene and dichloromethane are used as solvents, and the amount is based on the amount that can fully dissolve or immerse the raw materials.

[0026] Preparation Example 4 A modified styrene-ethylene-butylene-styrene block copolymer, which is different from Preparation Example 1 in that the acrylate used in this example is butyl acrylate.

[0027] Preparation Example 5 A modified styrene-ethylene-butylene-styrene block copolymer, which is different from Preparation Example 1 in that the acrylic acid ester used in this example is methyl methacrylate.

[0028] Preparation Example 6 A modified styrene-ethylene-butylene-styrene block copolymer is different from Preparation Example 1 in that the initiator used in this example is cyclohexane di(tert-amyl)peroxide. Example

[0029] Example 1 A low-hardness, high-temperature-resistant thermoplastic elastomer, the preparation of which comprises the following steps: (1) 100 kg of modified styrene-ethylene-butylene-styrene block copolymer and 250 kg of white oil were mixed uniformly at high speed to prepare an oil-extended SBES for later use; (2) The above-prepared oil-extended SBES, 8 kg antioxidant and 55 kg polypropylene were pre-mixed using a high-speed mixer, and melt-blended and extruded into granules using a twin-screw extruder at 210° C., with a rotation speed of 400 r / min and a feeding rate of 40 kg / h. The antioxidant was tris(nonylphenol)phosphite and 2,6-tert-butyl-4-methylphenol mixed in a ratio of 0.5:2, and the modified styrene-ethylene-butylene-styrene block copolymer was prepared in Preparation Example 1.

[0030] Example 2 A low-hardness, high-temperature-resistant thermoplastic elastomer, the preparation of which comprises the following steps: (1) 95 kg of modified styrene-ethylene-butylene-styrene block copolymer and 50 kg of white oil were mixed uniformly at high speed to prepare an oil-extended SBES for later use; (2) The above-prepared oil-extended SBES, 5 kg antioxidant and 10 kg polypropylene were pre-mixed using a high-speed mixer, and melt-blended and extruded into granules using a twin-screw extruder at 200° C., with a rotation speed of 400 r / min and a feeding rate of 40 kg / h. The antioxidant was tris(nonylphenol)phosphite and 2,6-tert-butyl-4-methylphenol mixed in a ratio of 0.5:2, and the modified styrene-ethylene-butylene-styrene block copolymer was prepared in Preparation Example 1.

[0031] Example 3 A low-hardness, high-temperature-resistant thermoplastic elastomer, the preparation of which comprises the following steps: (1) 100 kg of modified styrene-ethylene-butylene-styrene block copolymer and 250 kg of white oil were mixed uniformly at high speed to prepare an oil-extended SBES for later use; (2) The above-prepared oil-extended SBES, 8 kg antioxidant and 55 kg polypropylene were pre-mixed using a high-speed mixer, and melt-blended and extruded into granules using a twin-screw extruder at 220° C., with a rotation speed of 400 r / min and a feeding rate of 40 kg / h. The antioxidant was tris(nonylphenol)phosphite and 2,6-tert-butyl-4-methylphenol mixed in a ratio of 0.5:2, and the modified styrene-ethylene-butylene-styrene block copolymer was prepared in Preparation Example 1.

[0032] Example 4 A low-hardness, high-temperature-resistant thermoplastic elastomer is different from Example 1 in that the modified styrene-ethylene-butylene-styrene block copolymer prepared in Preparation Example 2 is used in this example.

[0033] Example 5 A low-hardness, high-temperature-resistant thermoplastic elastomer is different from Example 1 in that the modified styrene-ethylene-butylene-styrene block copolymer prepared in Preparation Example 3 is used in this example.

[0034] Example 6 A low-hardness, high-temperature-resistant thermoplastic elastomer is different from Example 1 in that the modified styrene-ethylene-butylene-styrene block copolymer prepared in Preparation Example 4 is used in this example.

[0035] Example 7 A low-hardness, high-temperature-resistant thermoplastic elastomer is different from Example 1 in that the modified styrene-ethylene-butylene-styrene block copolymer prepared in Preparation Example 5 is used in this example.

[0036] Example 8 A low-hardness, high-temperature-resistant thermoplastic elastomer is different from Example 1 in that the modified styrene-ethylene-butylene-styrene block copolymer prepared in Preparation Example 6 is used in this example.

[0037] Example 9 A low-hardness, high-temperature-resistant thermoplastic elastomer, which is different from Example 1 in that the antioxidant used in this example is 2,2'-ethylenebis(6-tert-butyl-4-methylphenol).

[0038] Example 10 A low-hardness, high-temperature-resistant thermoplastic elastomer, which is different from Example 1 in that 1 kg of sepiolite powder is further added in this example, and the preparation comprises the following steps: (1) 100 kg of modified styrene-ethylene-butylene-styrene block copolymer and 250 kg of white oil were mixed uniformly at high speed to prepare an oil-extended SBES for later use; (2) The oil-extended SBES prepared above was pre-mixed with 8 kg of antioxidant, 1 kg of sepiolite powder and 55 kg of polypropylene using a high-speed mixer, and melt-blended and extruded into granules using a twin-screw extruder at 210° C., with a rotation speed of 400 r / min and a feeding rate of 40 kg / h. The antioxidant was a mixture of tris(nonylphenol)phosphite and 2,6-tert-butyl-4-methylphenol in a ratio of 0.5:2, and the modified styrene-ethylene-butylene-styrene block copolymer was prepared in Preparation Example 1.

[0039] Embodiment 11 A low-hardness, high-temperature-resistant thermoplastic elastomer, which is different from Example 10 in that 3 kg of sepiolite powder is added in this example.

[0040] Comparative Example Comparative Example 1 A low-hardness, high-temperature-resistant thermoplastic elastomer, which is different from Example 1 in that an unmodified styrene-ethylene-butylene-styrene block copolymer is used in this comparative example.

[0041] Comparative Example 2 A low-hardness, high-temperature-resistant thermoplastic elastomer, which is different from Example 1 in that no polypropylene is added in this comparative example.

[0042] Performance testing Detection method / test method Shore A hardness test: Tested according to ISO-868, using a high-speed iron ShareA hardness tester, the test sample thickness is not less than 6mm, and the test reading is 15s; Thermal weight loss test: The prepared TPE material was continuously heated at 120°C for 50 hours to test the weight loss rate of the material; Thermal deformation test: Test the tensile strength before aging, record it, put the sample into a thermal aging box, keep it at 110℃ for 150 hours, and test the tensile strength again.

[0043] Table 1 Experimental data detection table Combining Examples 1-3 and Comparative Example 1 and Table 1, it can be seen that the various test data of Examples 1-3 are better than those of Comparative Example 1, indicating that the use of the modified SEBS prepared in the present application as the base material of the elastomer can introduce sacrificial bonds of hydrogen bond clusters that are better than the main chain breaking at high temperatures into the elastomer, thereby dissipating a large amount of energy and reducing the stress received by the main chain, thereby improving the heat resistance of the material, and in this process, no hard segment is introduced, thereby avoiding an increase in the hardness of the elastomer.

[0044] Combining Examples 1-3 and Comparative Example 2 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 2, indicating that the use of polypropylene can form a dual-continuous phase structure with SEBS, and the introduced groups after modification can further improve the high temperature resistance of the elastomer.

[0045] Combining Examples 1-7 and Table 1, it can be seen that the experimental data of Examples 1-6 are better than those of Example 7, indicating that the use of methyl acrylate and butyl acrylate can reduce the glass transition temperature of the obtained elastomer, and the introduction of the soft chain segments thereon further reduces the hardness of SEBS.

[0046] Combining Example 1 with Example 8 and Table 1, it can be seen that the experimental data of Example 1 are better than those of Example 8, indicating that the choice of initiator affects the grafting efficiency of the modified SEBS, thereby affecting the modification effect of SEBS, and further affecting the various properties of the final elastomer.

[0047] Combining Example 1 with Example 9 and Table 1, it can be seen that the experimental data of Example 1 are better than those of Example 9, indicating that the use of an antioxidant compounded with a phosphite and a hindered phenol antioxidant can bring better high temperature resistance to the elastomer, can cooperate to remove free radicals generated at high temperature, effectively inhibit the oxidative decomposition of the elastomer, and improve the heat resistance of the elastomer.

[0048] Combining Example 1 with Examples 10-11 and Table 1, it can be seen that the experimental data of Examples 10-11 are better than those of Example 1, indicating that further adding sepiolite powder as a raw material can bring better high temperature resistance to the elastomer. It has a unique fibrous structure that can help dissipate high temperature energy, thereby improving the high temperature resistance of the elastomer.

[0049] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A low-hardness, high-temperature-resistant thermoplastic elastomer, characterized in that: The composition comprises the following raw materials in parts by weight: 90-100 parts of modified styrene-ethylene-butylene-styrene block copolymer, 50-250 parts of white oil, 10-100 parts of polypropylene, and 5-10 parts of antioxidant, wherein hydrogen bonds formed by urea groups are introduced into the modified styrene-ethylene-butylene-styrene block copolymer, and the preparation comprises the following steps: (1) Dissolve styrene-ethylene-butylene-styrene block copolymer in xylene, heat to 110-130°C with stirring, add acrylate and initiator, stir and react for 1-2 hours. After the reaction is completed, pour the mixture into acetone, stir, filter, wash and dry to obtain a preliminarily modified SEBS; (2) The preliminarily modified SEBS obtained in step (1) is immersed in dichloromethane. After 3-4 hours, the swollen SEBS is transferred to a dichloromethane solution of 4-phenyl-1,2,4-triazolin-3,5-dione. After sufficient reaction for 11-13 hours, the SEBS is taken out, washed and vacuum dried to obtain the modified styrene-ethylene-butylene-styrene block copolymer.

2. The low-hardness, high-temperature-resistant thermoplastic elastomer according to claim 1, characterized in that: The weight proportion of the styrene-ethylene-butylene-styrene block copolymer, acrylate, initiator and 4-phenyl-1,2,4-triazine-3,5-dione added is 1:0.6-0.8:0.02-0.04:0.4-0.

6.

3. The low-hardness, high-temperature-resistant thermoplastic elastomer according to claim 1, characterized in that: The acrylate is any one of ethyl acrylate or butyl acrylate.

4. The low-hardness, high-temperature-resistant thermoplastic elastomer according to claim 1, characterized in that: The initiator is benzoyl peroxide.

5. The low-hardness, high-temperature-resistant thermoplastic elastomer according to claim 1, characterized in that: The antioxidant is a composite antioxidant obtained by mixing powdered phosphite and hindered phenol antioxidant in a weight ratio of 0.5:(2-3).

6. The low-hardness, high-temperature-resistant thermoplastic elastomer according to claim 1, characterized in that: The raw materials also include 1-3 parts of sepiolite powder.

7. A method for preparing a low-hardness, high-temperature-resistant thermoplastic elastomer according to any one of claims 1 to 6, characterized in that: The method comprises the following preparation steps: (1) Stirring and mixing styrene-ethylene-butylene-styrene block copolymer and white oil to obtain oil-extended SBES for later use; (2) The oil-filled SBES prepared above is pre-mixed with an antioxidant and polypropylene, and then melt-blended and extruded at 200-220°C to form pellets.

Citation Information

Cited By

  • TPE (thermoplastic elastomer) composition for protective film adhesive layer and preparation method of TPE composition

    CN120590893A

  • Tpe composition for a protective film adhesive layer and a method for preparing the same

    CN120590893B